GEOMETRICAL CONSTRUCTION TASK AS AN EFFECTIVE SOURCE OF 21st CENTURY SKILLS TRAINING - Proshkin, Vladimir; Astafieva, Maria; Radchenko, Svetlana (Educological discourse, 2017)
In this article it is disclosed the essence of a concept of skills of 21st century as pedagogical phenomenon. Three blocks of skills are allocated: educational and innovative skills; media and computer skills; vital and professional (career) skills. Critical thinking is considered as the leading skill of 21st century. Presented results of actual practice of formation of critical thinking of the modern youth presented, visually illustrate extremely low ability of youth to the analysis, analogies, and their inability to put the known (learned) facts into practice, in formally distinct situation. It is shown that the mathematics has inexhaustible opportunities and resources for training of critical, in particular, logical thinking, with observance of rules and laws of logic theory. Geometrical construction tasks are presented as a class of geometrical tasks which solution trains the thinking and promotes formation of a number of other skills of 21st century. It is noted that in a geometrical construction task it is required to construct a geometrical figure by means of particular drawing instruments, such as a ruler and compasses, when particular elements of this figure or other figures, connected with required figure in a certain manner, are set. Four stages of the solution process of geometrical construction tasks are characterized: analysis, creation, proof, research. It is noted that the solution of geometrical construction tasks is the classical solution of any (not only mathematical, but also industrial, social, household, etc.) problem and entire process of construction tasks solution is some kind of scientific research, creation of new knowledge for the pupil.